A remote electrocardiogram monitoring system with good swiftness and high reliablility. (July 2016) - Chen, Hanlin; Liu, Hongwei
Highlights: A Two-level Load-balance Monitoring Strategy (TLLBMS) is proposed. Parallel PCA-ICA Algorithm is realized to fulfill quick preprocessing and feature extraction. Only eigenvectors are transmitted at a Dynamically Variable Time Interval (DVTI). MD5 hash algorithm is realized to ensure the correctness of communication. Abstract: To solve the problems of long time delay and low reliability in existing systems, a Two-level Load-balance Monitoring Strategy (TLLBMS) is proposed in this paper. In monitoring terminal level, based on customizable System-on-Chip A2F500, monitoring terminals implement parallel Principal Component Analysis and Independent Component Analysis (PCA-ICA) algorithm to fulfil quickly preprocessing and feature extraction of electrocardiogram (ECG) signals, and give a pre-classification and alarming mechanism. Depending on the results of pre-classification, monitoring terminals transmit only eigenvectors to monitoring center at a Dynamically Variable Time Interval (DVTI). This will reduce the quantity of data transmission dramatically, which means it will lead to high robustness of communication and short time delay. In monitoring center level, monitoring server processes eigenvectors directly, and realizes quick classification, diagnosis and rescuing. To ensure the correctness of communication and protect data from being falsified, Message Digest Algorithm MD5 is realized to verify the integrity of data. Graphical abstract: